Analisis Pengaruh Pembelajaran Tematik Berbasis Proyek Untuk Meningkatkan Kreativitas Siswa SD - Marlin, Adinda Agesti; Afandi, Yogi; Syahfitri, Alda; Madani, Wisti; Kusuma W, Cleo Ratih; Zahara, Chacha Febryan; Muhtarom, Taufik (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the impact of implementing project-based thematic learning on enhancing the creativity of elementary school students. The method employed is a Systematic Literature Review (SLR) by examining five research articles published in nationally accredited journals from 2015 to 2025. The primary data sources are secondary data in the form of previous research articles, obtained through a systematic search using Google Scholar and other academic databases. Data collection was carried out by selecting articles based on the keywords "Project Based Learning" and "student creativity," using well-defined inclusion and exclusion criteria. The data were analyzed using a descriptive qualitative approach, focusing on learning models, implementation stages, and their effects on students' creativity. The results show that project-based thematic learning significantly improves students’ creative thinking skills, encourages active engagement in the learning process, and fosters critical thinking and problem-solving abilities. Therefore, this approach is proven to be an effective innovative learning strategy for developing student potential in 21st-century education.